Análise da variabilidade morfodinâmica de uma praia arenosa através do uso de funções ortogonais empíricas - Lima, Larissa Luana Lopes (2018)
The coastal zone behaves as a dynamic environmental system. One of the greatest challenges facing the scientific community is to hold a correct understanding of the functioning of this environment. A rather insightful analysis requires not only observations of nature, but also knowledge of the processes that work in the environment together with statistical methodologies. The empirical orthogonal function (EOF) was used to analyze beach profiles obtained during approximately a complete seasonal cycle, with the objective of identifying patterns of spatial and temporal changes of topography on a sandy beach with the presence of a rocky outcrop submerged in the city of Rio de Janeiro (Reserve Beach). Through the spatial analysis, a protrusion of approximately 150 m longitudinal was identified in the rear zone of the submerged rock outcrop. In addition, it was possible to notice that the western side and the rear region of the rock outcrop showed larger morphodynamic variations. The temporal analysis showed that the greatest erosive changes occurred in the period of higher significant wave height (hs). Although EOF is a tool used for the analysis of random data, it is possible to obtain physical interpretations of the predominant patterns in time, for example, from the relationship between periods of erosion with variables that act on the dynamics of the praial system (hs). Therefore, this method was efficient in the identification of morphological patterns in the time and can still be applied to analyze the response of the profiles to the action of the waves, if some strong relation between them is found.